(untitled) (Homoeopathy for All, 2024)
During the COVID-19 pandemic, wearing masks became one of the most effective measures to curb the spread of the virus. Masks protect both the wearer and those around them by filtering out harmful respiratory droplets, which can carry viruses. As a simple yet powerful tool, masks not only helped prevent the transmission of COVID-19 but also raised awareness of their broader benefits in reducing the spread of other infectious diseases and improving overall public health. But wearing masks for extended periods can contribute to various skin problems, including acne, irritation, and rashes. To minimize mask-related acne, it’s important to keep face and mask clean, use breathable fabrics, and maintain a proper skincare routine. Along with this, Homeopathy can play a major role in managing maskne by addressing the underlying causes of skin imbalance and promoting natural healing.